Comparing Natural History of Early and Late Onset Pediatric Multiple Sclerosis. Issue 4 (28th February 2022) - De Meo, Ermelinda; Filippi, Massimo; Trojano, Maria; Comi, Giancarlo; Patti, Francasco; Brescia Morra, Vincenzo; Salemi, Giuseppe; Onofrj, Marco; Lus, Giacomo; Cocco, Eleonora; Fonderico, Mattia; Torri Clerici, Valentina; et al.
Abstract : Objective: This study was undertaken to describe and compare disease course and prognosis of early (ie, disease onset before age 11 years) and late (ie, disease onset after age 11 years) onset pediatric multiple sclerosis. Methods: Prospectively collected clinical information from Italian Multiple Sclerosis Register of 1993 pediatric multiple sclerosis patients, of whom 172 had early onset, was analyzed. Cox models adjusted for sex, baseline Expanded Disability Status Scale score, and disease‐modifying treatments and stratified for diagnostic criteria adopted (Poser vs McDonald) were used to assess the risk of reaching irreversible Expanded Disability Status Scale scores of 3, 4, and 6, and conversion to secondary progressive phenotype in early versus late onset pediatric patients. Prognostic factors were also evaluated. Results: A greater proportion of males, isolated brainstem involvement, and longer time interval between first and second clinical episode were observed in early versus late onset pediatric patients. Compared to late onset, early onset pediatric patients took longer from disease onset to convert to secondary progressive phenotype and to reach all disability milestones. Recovery from first demyelinating event, time to first relapse, annualized relapse rate during the first 3 years of disease, and disease‐modifying treatment exposure were independent predictors for long‐term disability in early onset pediatric patients. In late onset pediatric patients, isolated optic neuritis, multifocal symptoms, and progressive course at disease onset were additional predictors for long‐term disability. Interpretation: These findings point toward the existence of a different natural history in early versus late onset pediatric multiple sclerosis patients. ANN NEUROL 2022;91:483–495